The Effect of Propylene Glycol and Menthol as Enhancers on the Physical Properties and Skin Irritation Index of Meloxicam Gel - Asa Falahi; Anies Rohman (LPPM Universitas dr. Soebandi, 2025)
Abstract Background: The drawback of meloxicam when used orally is that it slows the onset time of meloxicam. Other side effects of oral use include gastrointestinal disorders, dyspepsia, nausea, diarrhea, upper gastrointestinal infections, abdominal pain, swelling, and bloating. These side effects have been reported in 15–20% of patients. There is a need to develop a transdermal meloxicam formulation with a modified penetration system. Purpose: This study aims to develop a formulation of meloxicam gel preparations with a direct release system towards the skin barrier and within a period of time is extended by using 10% propylene glycol and 3% menthol as an enhancer to get the optimum formula of meloxicam gel with good physical properties and does not irritate the skin. Methods: This research method is a laboratory experimental study. Gel preparations were made by varying the enhancer agents, namely propylene glycol and menthol. The gel preparations were made by developing the gelling agent to an optimal level. Other additional ingredients were mixed with various enhancer variations. Results: The observed physical properties of the gel included organoleptic characteristics, pH, viscosity, spreadability, and irritation tests. Overall, the test results showed data that met the applicable requirements. All four formulas showed significant differences in each test and did not show signs of skin irritation. Conclusions: The results show that variation concentration of enhancer has an effect to gel form, smell viscosity and spreadability but has no effect to gel colour and pH. All formulas show not irritate the skin.